DETERMINAN KUALITAS LAPORAN KEUANGAN SATUAN KERJA DI WILAYAH PEMBAYARAN KANTOR PELAYANAN PERBENDAHARAAN NEGARA MATARAM - Mohammad Roni; Lalu Hamdani Husnan; Nur Fitriah (Universitas Negeri Malang, 2015)
The object of this research is to know the effect of the factor Governmental Accounting Standard apllying, human resource competencies, Information technology utilization, and reconciliation to the financial statements quality of the working unit in payment with KPPN Mataram. The population in this research are 312 units, spread throughout 45 Ministries/Agencies. Samples taken in the research of 80 working units using purposive sampling technique. Each sample represented one respondent treasury officials is the Treasurer. Questionnaires were distributed to 80 respondents, successfully reassembled by 80 respondents. Collected data were analyzed using multiple linear regression analysis of SPSS Version 21.00. Based on the results of data analysis, it was concluded that the Governmental Accounting Standard apllying and information technology using signifikan positive effect on the quality of financial statements of working unit in payment with KPPN Mataram. While the human resourcecompetencies and reconciliation does not significantly influence the quality of financial statements.Keywords: Gavermental Accounting Standards (GAS), competence of the human resources, information technology utilization, reconciliation, and quality of financial statements